Effects of submaximal cycling and long-term endurance training on neutrophil phagocytic activity in middle aged men. Issue 2 (June 1996) - Blannin, A K; Chatwin, L J; Cave, R; Gleeson, M
Abstract : OBJECTIVE: To investigate the effects of long term (> 10 years) endurance training and submaximal exercise on the phagocytic activity of circulating neutrophil granulocytes. METHODS: The ability of stimulated blood neutrophils isolated from well trained cyclists [n = 8; VO2max 61.0(SD 8.8) ml.kg-1.min-1; age 38(4) years] and age matched sedentary controls [n = 8; VO2max 37.4 (6.6) ml.kg-1.min-1] to ingest nitroblue tetrazolium was assessed at rest and following a standardised submaximal bout of exercise on a cycle ergometer. RESULTS: Trained subjects had a lower resting blood neutrophil count (P < 0.01). Acute exercise caused a rise (P < 0.01) in the blood neutrophil count irrespective of training status, but the magnitude of the rise was smaller in the trained subjects (P < 0.05). The circulating neutrophil phagocytic capacity was approximately 70% lower in trained individuals at rest compared with the control subjects (P < 0.01). Acute submaximal exercise increased this variable in both groups, but phagocytic capacity remained substantially lower in the trained subjects compared with the controls (P < 0.05) despite the observation that a higher proportion of the circulating neutrophils were stimulated to undergo phagocytosis in the trained subjects [57(14)% v 32(7)%; P < 0.01). CONCLUSIONS: Although neutrophil phagocytic activity is only one variable that contributes to immunological status, prolonged periods of endurance training may lead to increased susceptibility to opportunistic infections by diminishing this activity at rest.